What Kind of Unionism: Struggles Among Sydney Steel Workers in the SWOC Years, 1936-1942 - Crawley, Ron (Labour/Le Travailleur, 1997)
In late 1936 steel worker activists in Sydney launched a new organizing drive at the plant under the auspices of the CIO's Steel Workers Organizing Committee(SWOC). This effort drew the support of steel workers in a way that previous organizing attempts had not. However, the militant and self-reliant traditions of the steel workers collided with the cautious strategies and bureaucratic practices of the appointed SWOC leadership in the United States and Canada. As steel workers at Sydney showed great solidarity in their struggle with DOSCO, they also resisted what they saw as undemocratic and highly accommodationist practices by the union's national and international leadership. The struggles within the union embraced the issues of Canadian autonomy and nationalism as well as rank-and-file union control and the democratic rights of union members. It amounted to a struggle over what type of unionism was to be established within the Canadian steel industry.